The Effect of Local Taxes, General Allocation Funds, and Special Allocation Funds on Capital Expenditures of the Government of South Sumatra Province 2010 - 2019 - Ayunda Dina Maharani; Harsi Romli; Vhika Meiriasari (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to examine the effect of local taxes, general allocation funds and special allocation funds on the capital expenditure of the South Sumatra Province government for the 2010-2019 period. The data used in this study are primary and secondary. Furthermore, the data were analyzed using multiple linear regression. This study prove that the general allocation funds have a positive effect on the capital expenditure of the South Sumatra provincial government. While, local taxes and special allocation funds are not proven to have a positive effect on the capital expenditure of the South Sumatra provincial government. Furthermore, the test results of the coefficient of determination (R2) obtained a value of 0,773. This shows that the amount of the contribution of the tax variables, general allocation funds and special allocation funds can explain the capital expenditure of 77,30% the remaining is influenced by other variables included in this study.